Switchable Fluorescence of a Mechanical Stimulus-Responsive Au-P-S Complex - Jieqiong Huang; Yuanyuan Hu; Wendi Xu; Wei Yang; Chengrong Lu; David James Young; Zhi-Gang Ren (Molecules)
The reaction of [(3-bdppmapy)(AuCl)2] with NaHmna (3-bdppmapy = N,N’-bis-(diphenylphosphanylmethyl-3-aminopytidine, H2mna = 2-mercaptonicotinic acid)) resulted in a tetranuclear Au-P-S complex [(3-bdppmapy)2(AuHmna)2(AuCl)2] (1) which emitted bright yellow fluorescence at 542 nm under 377 nm excitation (QY = 5.3%, τ = 0.83 ns). Upon grinding, the emission intensity of 1 significantly and rapidly decreased, but could be recovered by exposure to CH2Cl2 vapor. This switchable fluorescence is attributed to the breaking and reforming of intermolecular hydrogen bonds with concomitant collapse and the restoration of the crystalline phase, which is not caused by static pressure or increased temperature.